(untitled) (European Journal of Education and Psychology, 2018)
The aim of the present study was to empirically test an explanatory model of psychosocial adjustment during adolescence, with psychosocial adjustment during this stage being understood as a combination of school adjustment (or school engagement) and subjective well-being. According to the hypothetic model, psychosocial adjustment depends on self-concept and resilience, which in turn act as mediators of the influence of perceived social support (from family, peers and teachers) on this adjustment. Participants were 1250 secondary school students (638 girls and 612 boys) aged between 12 and 15 years (Mean = 13.72; SD = 1.09). The results provided evidence of: (a) the influence of all three types of perceived support on subject resilience and self-concept, with perceived family support being particularly important in this respect; (b) the influence of the support received from teachers on school adjustment and support received from the family on psychological wellbeing; and (c) the absence of any direct influence of peer support on psychosocial adjustment, although indirect influence was observed through the psychological variables studied. These results are discussed from an educational perspective and in terms of future research.